1998
DOI: 10.1523/jneurosci.18-01-00451.1998
|View full text |Cite
|
Sign up to set email alerts
|

Hypoactivity of the Spinal Cannabinoid System Results in NMDA-Dependent Hyperalgesia

Abstract: Cannabinoids, such as Delta9-THC, are capable of inhibiting nociception, i.e., pain transmission, at least in part, by interacting with spinal Gi/Go-coupled cannabinoid receptors. What is not known, however, is the antinociceptive role of endogenous spinal cannabinoids. If endogenous cannabinoids modulate basal nociceptive thresholds, then alterations in this system could be involved in the etiology of certain pain states. In this report we provide evidence for tonic modulation of basal thermal nociceptive thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(88 citation statements)
references
References 23 publications
6
82
0
Order By: Relevance
“…Moreover, blockade of the CB1 receptor with the antagonist SR141716A produces hyperalgesia (37,38) and stimulates locomotor activity (39). The differences between the pharmacological results and this genetic study may be accounted for by the inverse agonist properties of SR141716A (40), or by differences in acute vs. chronic inactivation of the CB1 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, blockade of the CB1 receptor with the antagonist SR141716A produces hyperalgesia (37,38) and stimulates locomotor activity (39). The differences between the pharmacological results and this genetic study may be accounted for by the inverse agonist properties of SR141716A (40), or by differences in acute vs. chronic inactivation of the CB1 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Although binding studies have found peripheral tissues to be negative for cannabinoid binding sites (Jansen et al, 1992;Lynn and Herkenham, 1994;RinaldiCarmona et al, 1996), CB 1 cannabinoid receptor mRNA is detectable in a number of peripheral tissues (Galiègue et al, 1995;. We have previously demonstrated that activation of spinal CB 1 receptors can result in both antihyperalgesia and inhibition of neuropeptide release from central terminals of capsaicin-sensitive primary afferent nociceptive fibers (Richardson et al, 1998b). Additionally, we have demonstrated that cannabinoid binding sites can be measured in sensory neurons (Richardson et al, 1998b).…”
Section: Introductionmentioning
confidence: 92%
“…We have previously demonstrated that activation of spinal CB 1 receptors can result in both antihyperalgesia and inhibition of neuropeptide release from central terminals of capsaicin-sensitive primary afferent nociceptive fibers (Richardson et al, 1998b). Additionally, we have demonstrated that cannabinoid binding sites can be measured in sensory neurons (Richardson et al, 1998b). Hohmann and Herkenham (1997) have reported that CB 1 receptor mRNA is expressed in substance P containing neurons in the dorsal root ganglia.…”
Section: Introductionmentioning
confidence: 96%
“…CB 1 receptors are also expressed in the dorsal root ganglia by a subset of small-and large-diameter sensory neurons that contain the pain-stimulating peptides, substance P and ␣-calcitonin gene-related peptide (CGRP) 32 . Although quantitatively small, the presence of CB 1 receptors on CGRPcontaining neurons appears to be functionally significant because CB 1 receptor agonists effectively reduce CGRP release from dorsal horn tissue 33 . Immunohistochemical experiments suggest that CB 1 receptors are present not only on central terminals of primary sensory afferents, but also on their peripheral counterparts 34 (Fig.…”
Section: Modulation Of Painmentioning
confidence: 99%